The Male-Child and the Principle of Reality in African Society: Educating the Male-Child away from the Grips of the Pleasure Principle towards the Reality Principle and Productivity through the Symbolic Order: A Transformative Perspective from Amu Djoleto in his 'The Strange Man' (Global Journal of Medical Research, 2023)
In two articles in the London Journal of Research and Social Sciences (IJRISS), (2019 & 2021), I explored, sequentially, the argument regarding the process of the formation of the human subject and how crucial it is for the individual's growth process to be moulded through integration into the symbolic order to enable human growth, development and maturation, mental stability, the formation of identity and individuality, and preparation for the need to labour. The outcome of such growth and process is being able to focus on a stable object and being able to become productive, and above all, capable of promoting the development of sound mental health and civilization.
Keywords: The male-child; human subject; identity; symbolic order; pleasure principle; reality principle; eternal infantilism; mental health